TANGGUNG JAWAB AMERIKA SERIKAT ATAS JATUHNYA PUING SPACEX DRAGON DI AUSTRALIA AKIBAT KEGIATAN KOMERSIALISASI BERDASARKAN LIABILITY CONVENTION 1972: The United States’ Liability for the Fall of SpaceX Dragon Debris in Australia due to Commercialization Activities based on the Liability Convention 1972 - Lingga Ayu Winusratu; Sugeng Supartono (Faculty of Law, Universitas Trisakti, 2025)
According to the Outer Space Treaty, commercial space activities by private entities are regulated, but it is implicitly stated that countries must make their own policies regarding this matter. The problem is how countries hold responsibility under the Liability Convention of 1972 and how the United States will hold SpaceX accountable for the falling debris of the SpaceX Dragon in Australia as a result of commercialized space activities. The research was conducted with a normative research methodology and secondary data, data collection was done through library studies, analyzed using qualitative methods, and conclusions were drawn using deductive methods. The research results indicate that according to the Liability Convention of 1972, the Launching State is responsible for any damage or impacts caused by space activities. The characterization of the element of state responsibility in the United States can be delegated, therefore, the United States, acting as NASA, is not held responsible for the falling debris of the SpaceX Dragon in Australia.